New Zinc Binding Motifs in the Design of Selective Carbonic Anhydrase Inhibitors - Winum, Jean-Yves; Scozzafava, Andrea; Montero, Jean-Louis; Supuran, Claudiu T. (Mini Reviews in Medicinal Chemistry, 2006)
The carbonic anhydrases (CAs, EC 4.2.1.1) are ubiquitous zinc enzymes which catalyze a very simple physiological reaction, the interconversion between carbon dioxide and the bicarbonate ion, and are involved in physiological and pathological processes. The different isozymes have been considered as important targets for inhibitors with clinical applications. Several sulfonamide carbonic anhydrase inhibitors (CAIs) were used for decades as diuretics, anti-glaucoma, anti-epileptic, anti-ulcer agents, or as drugs for treating other neurological/neuromuscular disorders, whereas presently several such agents still find wide applications in therapy, mainly as topically acting anti-glaucoma drugs, anti-cancer, or anti-obesity agents. Although sulfonamides were considered the moiety par excellence to coordinate the catalytic zinc and for designing potent CAIs, in recent years related functional groups such as sulfamate, sulfamide and others have proven to be successful in the design of selective CAIs. The present review will deal with these different zinc binding functions recently reported in literature.
Keywords: Cyanamide